2014
DOI: 10.6018/analesps.30.2.161251
|View full text |Cite
|
Sign up to set email alerts
|

El papel moderador de la autoeficacia profesional entre situaciones de acoso laboral y la salud en una muestra multiocupacional

Abstract: Resumen: La autoeficacia es una competencia personal que actúa frente a los estresores incrementando o disminuyendo el malestar psicológico que estos pueden generar; por su parte el acoso psicológico o mobbing es uno de los factores psicosociales del medio laboral más dañinos para la salud de los trabajadores. Utilizando como marco de referencia el modelo teórico de demandas-recursos (JD-R model), este trabajo tiene como objetivo principal analizar el papel moderador de la autoeficacia profesional entre el aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
5
0
3
Order By: Relevance
“…According to the results of this study, resilient people are better adapted to this psychosocial stressor and therefore enjoy higher perceived health despite exposure to adversity. Studies analysing other personal resources in situations of workplace bullying have shown that moderating roles, when they are present, are most relevant at lower levels of perceived bullying and disappear at higher levels (Lokke et al, 2011;Matthiesen & Einarsen, 2004;Meseguer et al, 2014;Mikkelsen & Einarsen, 2002;Nielsen, Matthiesen, & Einarsen, 2008). However, according to our results, resilience also reduces discomfort in situations where serious bullying is perceived.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…According to the results of this study, resilient people are better adapted to this psychosocial stressor and therefore enjoy higher perceived health despite exposure to adversity. Studies analysing other personal resources in situations of workplace bullying have shown that moderating roles, when they are present, are most relevant at lower levels of perceived bullying and disappear at higher levels (Lokke et al, 2011;Matthiesen & Einarsen, 2004;Meseguer et al, 2014;Mikkelsen & Einarsen, 2002;Nielsen, Matthiesen, & Einarsen, 2008). However, according to our results, resilience also reduces discomfort in situations where serious bullying is perceived.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, the role played by personal resources in the relationship between mobbing and health is not clear. Studies that have analysed other personal resources, such as generalised self-efficacy (Matthiesen & Einarsen, 2004), professional self-efficacy (Meseguer, Soler, & García-Izquierdo, 2014), negative affectivity (Mikkelsen & Einarsen, 2002), sense of coherence (Nielsen, Matthiesen, & Einarsen, 2008), hardiness (Rekness et al, 2018), or self-labelling (Lokke, Glaso, & Einarsen, 2011), have shown that these resources moderate the relationship between workplace bullying and health. However, the few studies that have analysed the role of resilience have discovered that it works as a mediating variable between workplace bullying and health (Lokke et al, 2011;Maidaniuc-Chirila 2015a, 2015b.…”
Section: Palabras Clavementioning
confidence: 99%
See 1 more Smart Citation
“…Selfefficacy provides people with confidence regarding their capacity to take control over different life aspects. In this manner, self-efficacy would be a personal competence that works triggered by stressors, increasing or decreasing the psychological discomfort that they could generate (Meseguer, Soler, & García-Izquierdo, 2014). In fact, people who show high self-efficacy levels are also confident about their ability to respond to external stimuli, influencing their way to perceive and process environmental demands or threats (Salanova, Grau, & Martínez, 2005).…”
Section: Self-efficacy As An Antecedent Of Work Design and Job Satisfmentioning
confidence: 99%
“…El supuesto teórico de la TSC sobre la autoeficacia es contrastable en el mundo del trabajo y las organizaciones laborales. La autoeficacia cumple el papel de moderador (Jex, Bliese, Buzzell & Primeau, 2001) minimizando el impacto de las demandas laborales como la sobrecarga cuantitativa (Jex & Bliese, 1999;Salanova, Grau et al, 2005), la rutina (Grau, Salanova & Peiró, 2012) y el acoso laboral (Meseguer, Soler & García-Izquierdo, 2014). Así también, influye de forma inversa sobre consecuentes relacionados con el malestar psicosocial, tales como el síndrome de burnout (Evers, Brouwers & Tomic, 2002;Gil-Monte, García-Juesas & Caro, 2008) o el presentismo laboral (Lu, Peng, Yen & Cooper, 2014) y, de manera directa con constructos vinculados bienestar como el engagement (Consiglio, Borgogni, Di Tecco & Schaufeli, 2005;Juárez, 2015;Xanthopolou, Bakker, Demerouti & Schaufeli, 2007) o la satisfacción en el trabajo (Boluarte & Merino, 2015;Klassen & Chiu, 2010;Siu, Spector, Cooper & Lu, 2014;Yañez, Arenas, & Ripoll, 2010).…”
Section: Introductionunclassified